Melanoma in the head and neck region. - Avello Canisto, Francisco (2015)
Melanoma consists in malignant degeneration and atypia of melanocytes (melanin pigment forming cells). Melanocytes are found in skin (basal layer of epidermis), eye (choroid membrane) and central nervous system (pia mater). Location in head and neck represents 30% of all melanomas, following upper and lower extremities localization, and over two-thirds are located in the skin of the face. Origin in the mucous membranes (nose, oral cavity, and conjunctiva) is less common and usually lacks melanin. There are reports of intraocular and submandibular salivary gland melanomas, but these presentations are very rare.